Parent's Relative Perceived Work Flexibility Compared to Their Partner Is Associated With Emotional Exhaustion - Leineweber, Constanze; Falkenberg, Helena; Albrecht, Sophie C. (Frontiers in Psychology, 2018)
A number of studies have found that control over work conditions and hours is positively related to mental health. Still, potential positive and negative effects of work flexibility remain to be fully explored. On the one hand, higher work flexibility might provide better opportunities for recovery. On the other hand, especially mothers may use flexibility to meet household and family demands. Here, we investigated the association between parent’s work flexibility, rated relative to their partner, and emotional exhaustion in interaction with gender. Additionally, gender differences in time use were investigated. Cross-sectional analyses based on responses of employed parents to the 2012 wave of the Swedish Longitudinal Occupational Survey of Health (SLOSH) were conducted (N=2,918). Generalized linear models with gamma distribution and a log-link function were used to investigate associations between relative work-flexibility (lower, equal or higher as compared to partner), gender and emotional exhaustion. After control for potential confounders, we found that having lower work flexibility than the partner was associated with higher levels of emotional exhaustion as compared to those with higher relative work flexibility. Also, being a mother was associated with higher levels of emotional exhaustion, independent of possible confounders. A trend towards an interaction effect between low relative work flexibility and gender was found in relation to emotional exhaustion. Regarding time use, clear differences between mothers’ and fathers’ were found. However, few indications were found that relative work flexibility influenced time use. Mothers spent more time on household chores as compared to fathers, while fathers reported longer working hours. Fathers spent more time on relaxation compared with mothers. To conclude, our results indicate that lower relative work flexibility is detrimental for mental health both for mothers and fathers. However, while gender seems to have a pronounced effect on time use, relative work flexibility seems to have less influence on how time is used. Generally, mothers tend to spend more time on unpaid work while fathers spend longer hours on paid work and report more time for relaxation.